2016
DOI: 10.1371/journal.pone.0161090
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Black or White-Gold? Early Stage Processing and the Color of 'The Dress'

Abstract: PurposeIn Feb 2015 an image of a dress posted on Tumblr triggered an internet phenomenon: Is the Dress blue and black (BB) or white and gold (WG)? Many claim BB and others insist WG while the true colors are BB. The prevailing theory is that assumptions about the illuminant govern perception of the Dress with WG due to bluish lighting and BB due to yellowish. Our purpose was to determine if early stage optical, retinal and/or neural factors also impact perception of the Dress.MethodsThirty-nine subjects were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…Additionally, in our data, variability in the asymmetric modulations to green-red stimuli also occurs across observers, but is unlikely to be correlated with the (negligible) differences in the relative perceptual salience of the red and green hues. As noted, one previous study investigating neural markers of perception of the dress found small group-level differences in early-stage cortical processing (Rabin et al, 2016). Here, stimulus sets were balanced for precortical color signals, such that while other early-level processes might contribute to the percepts, they are unlikely to be the primary factor.…”
Section: Perceptual Differences: White-gold Versus Blue-black Observersmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, in our data, variability in the asymmetric modulations to green-red stimuli also occurs across observers, but is unlikely to be correlated with the (negligible) differences in the relative perceptual salience of the red and green hues. As noted, one previous study investigating neural markers of perception of the dress found small group-level differences in early-stage cortical processing (Rabin et al, 2016). Here, stimulus sets were balanced for precortical color signals, such that while other early-level processes might contribute to the percepts, they are unlikely to be the primary factor.…”
Section: Perceptual Differences: White-gold Versus Blue-black Observersmentioning
confidence: 82%
“…This effect was interpreted as modulation of the percepts by top-down, post-perceptual processes. Other studies have pointed instead at low-level visual influences, such as spectral sensitivity differences from variations in macular pigment density (Rabin et al, 2016) or normal variations in pupil diameter (Vemuri et al, 2016). In this vein, neural correlates of visual evoked potential waveforms at a single medial-occipital electrode with differences in perception of the dress were reported (Rabin et al, 2016), although these low-level findings were not reliable at the individual participant level.…”
Section: Introductionmentioning
confidence: 89%
“…In principle, this variation could be due to low-level (individual differences in the sensory apparatus itself) or high-level (individual differences in feedback to the visual system) factors or both. One attempt to explain individual differences in terms of low-level effects was provided by Rabin, Houser, Talbert, and Patel (2016). They measured the macular pigment optical density (MPOD) and related it to the subjective experience of the color of the dress stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the two studies show a large variation in performance on this task between individuals. Other researchers have also found individual differences in performance in lightness constancy experiments [ 37 ], colour constancy [ 53 , 54 , 55 ] and gloss perception [ 26 ].…”
Section: Discussionmentioning
confidence: 99%